Preferences over social risk: does (group) size matter? - Andrea Morone; Tiziana Temerario (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we first replicated Harrison et al. (2012). Then, we studied if the group's size has an impact on group's risk aversion. In line with Harrison et al. (2012), our results confirm that no significant differences occur between individuals and groups risk aversion in three-person group. We also found that group size does not affect the level of risk aversion.
Keywords: C91; C92; D01; 330; Risk attitude; Preferences